Tertiary marine prosobranchs: larval dispersal and geographic range - Phillips, Susan Elizabeth Penny (Virginia Tech, 1993)
Scheltema (1971, 1978) and others have proposed that extensive larval dispersal allows marine invertebrate species to establish great geographic ranges; several studies along a single margin of an ocean basin have supported this proposal (Shuto, 1975; Hansen, 1978). This study makes use of the fossil record to examine larval dispersal patterns on a larger geographic scale: across an entire ocean basin. Sixteen genera/subgenera of marine prosobranch gastropods were selected as the data base for the study. Eight of the genera were widely distributed (have fossil representatives on both the eastern and western margins of the North Atlantic Ocean) during the Neogene, and eight genera were narrowly distributed (fossil representatives were restricted to either the eastern or the western margin of the North Atlantic) during the Neogene. The larval forms of fossil species within each genus were inferred by examination of protoconch morphologies, according to guidelines established by modern biologists (Robertson, 1974; Shuto, 1975). The two groups were compared using statistical methods to test a null hypothesis of no relationship between geographic distribution and larval form. The results of the study reject the null hypothesis, and support the conclusion that Neogene marine prosobranch genera that are widely distributed across the North Atlantic Ocean basin are much more likely to exhibit planktotrophic larval development than are prosobranch genera that are geographically limited to a single margin of the ocean basin. Master of Science